A review of recent advances in ZnO nanostructured thin films by various deposition techniques - Fatema Tuz Zohora Toma; Md Sharifur Rahman; Kazi Hanium Maria (Discover Materials)
Abstract This manuscript provides a comprehensive review of Zinc Oxide (ZnO) thin-film by various deposition techniques, primarily focusing on Chemical Bath Deposition (CBD), Spin Coating, Spray Pyrolysis, Thermal Evaporation, and Chemical Vapor Deposition (CVD) in the methodology section. This study is novel in its approach to systematically compare these widely used techniques alongside emerging and hybrid methods including Atomic Layer Deposition (ALD), Pulsed Laser Deposition (PLD), Hydrothermal Synthesis, Magnetron Sputtering, Electrodeposition, Electrospray Deposition, and the Sol–Gel Method thus offering a unified perspective on ZnO thin-film fabrication. The comparative analysis indicates key findings such as CBD and Spin Coating yield high optical transparency (85–92%) and intense band gaps (2.59–3.37 eV), making them ideal for gas-sensing and UV-blocking applications. Spray Pyrolysis and Thermal Evaporation produce compact films with particle sizes between 25–80 nm, offering properties advantageous for transparent electrodes and optoelectronic devices. Specifically, CVD and ALD exhibit preferable electrical properties with low resistivity (10⁻4–10⁻5 Ω cm) and high carrier mobility (50–100 cm2/V s), supporting high-performance electronics and nanoelectronics. Furthermore, hydrothermal Synthesis and PLD produce nanostructured thin films with high surface areas, suitable for catalysis, biosensing, and other applications. By presenting a thorough comparison across multiple techniques and identifying optimal deposition methods for various applications, this study contributes a critical resource for ZnO thin-film properties to meet specific technological requirements. The novelty of this work lies in its holistic evaluation of both traditional and advanced deposition methods, offering essential insights for next-generation ZnO thin-film applications in optoelectronics, sensors, biomedical, environmental, and sustainable technologies.